Complete genome sequence of burkholderia cenocepacia phage mica - Garcia, James (2021)
Burkholderia cenocepacia is a multidrug-resistant Gram-negative pathogen known to colonize patients with chronic granulomatous disease and cystic fibrosis. Here, we describe Burkholderia phage Mica, which is predicted to be a lysogenic myophage based on the similarity of its structural proteins to Enterobacteria phage P2 and Burkholderia phage KL3.